The visual handbook of building and remodeling : a comprehensive guide to choosing the right materials and systems for every part of your home - Wing, Charles, 1939- (Newtown, CT : Taunton Press, Inc., 2017)
"This new edition has 48 pages of brand-new material including new chapters on solar power and best-practice insulating as well as the latest code information and updated sections on framing, sheathing, air sealing, and heating and cooling, enabling the reader to visualize exactly how to tackle any building project or problem."--Amazon.com.
Design -- Site and Climate -- Masonry -- Foundations -- Wood -- Framing -- Sheathing -- Siding -- Roofing -- Windows and Doors -- Plumbing -- Wiring -- Insulation and R-Value -- Best Practice Insulating -- Air-Sealing Existing Buildings -- Floors, Walls, and Ceilings -- Storage -- Heating -- Cooling -- Passive Solar -- Lighting -- Sound -- Fasteners -- Decks and Railings -- Measuring and Finance.
Includes bibliographical references (pages 668-672) and index.
Keywords: House construction -- Handbooks, manuals, etc; Dwellings -- Remodeling -- Handbooks, manuals, etc; Building materials -- Handbooks, manuals, etc; House construction -- Pictorial works; Dwellings -- Remodeling -- Pictorial works